Page 1
Question:4
Write two solutions for each of the following equations:
Page 2
Question:4
Write two solutions for each of the following equations:
i
3x + 4y = 7
ii
x = 6y
iii
x + xy = 4
iv
2
3
x -y = 4
Solution:
i We are given,
Substituting x = 1 in the given equation, we get
Substituting x = 2 in the given equation, we get
i i We are given,
Substituting in the given equation, we get
Substituting in the given equation, we get
i i i We are given,
Page 3
Question:4
Write two solutions for each of the following equations:
i
3x + 4y = 7
ii
x = 6y
iii
x + xy = 4
iv
2
3
x -y = 4
Solution:
i We are given,
Substituting x = 1 in the given equation, we get
Substituting x = 2 in the given equation, we get
i i We are given,
Substituting in the given equation, we get
Substituting in the given equation, we get
i i i We are given,
Substituting x = 0 in the given equation, we get
Substituting x = 4 in the given equation, we get
i v We are given,
Substituting x = 0 in the given equation, we get
Substituting x = 3 in the given equation, we get
Question:5
Check which of the following are solutions of the equations 2x - y = 6 and which are not:
i
3, 0
ii
0, 6
iii
2, -2
iv
v
3, 0
( )
Page 4
Question:4
Write two solutions for each of the following equations:
i
3x + 4y = 7
ii
x = 6y
iii
x + xy = 4
iv
2
3
x -y = 4
Solution:
i We are given,
Substituting x = 1 in the given equation, we get
Substituting x = 2 in the given equation, we get
i i We are given,
Substituting in the given equation, we get
Substituting in the given equation, we get
i i i We are given,
Substituting x = 0 in the given equation, we get
Substituting x = 4 in the given equation, we get
i v We are given,
Substituting x = 0 in the given equation, we get
Substituting x = 3 in the given equation, we get
Question:5
Check which of the following are solutions of the equations 2x - y = 6 and which are not:
i
3, 0
ii
0, 6
iii
2, -2
iv
v
3, 0
( )
v
1
2
, -5
Solution:
We are given,
2x – y = 6
i In the equation 2x – y = 6,we have
Substituting x = 3 and y = 0 in 2x – y, we get
is the solution of 2x – y = 6.
i i In the equation 2x – y = 6, we have
Substituting x = 0 and y = 6 in 2x – y,we get
is not the solution of 2x – y = 6.
i i i In the equation 2x – y = 6,we have
Substituting x = 2 and y = –2 in 2x – y, we get
is the solution of 2x – y = 6.
i v In the equation 2x – y = 6, we have
Substituting and y = 0 in 2x – y, we get
is not the solution of 2x – y = 6.
v In the equation 2x – y = 6, we have
( )
Page 5
Question:4
Write two solutions for each of the following equations:
i
3x + 4y = 7
ii
x = 6y
iii
x + xy = 4
iv
2
3
x -y = 4
Solution:
i We are given,
Substituting x = 1 in the given equation, we get
Substituting x = 2 in the given equation, we get
i i We are given,
Substituting in the given equation, we get
Substituting in the given equation, we get
i i i We are given,
Substituting x = 0 in the given equation, we get
Substituting x = 4 in the given equation, we get
i v We are given,
Substituting x = 0 in the given equation, we get
Substituting x = 3 in the given equation, we get
Question:5
Check which of the following are solutions of the equations 2x - y = 6 and which are not:
i
3, 0
ii
0, 6
iii
2, -2
iv
v
3, 0
( )
v
1
2
, -5
Solution:
We are given,
2x – y = 6
i In the equation 2x – y = 6,we have
Substituting x = 3 and y = 0 in 2x – y, we get
is the solution of 2x – y = 6.
i i In the equation 2x – y = 6, we have
Substituting x = 0 and y = 6 in 2x – y,we get
is not the solution of 2x – y = 6.
i i i In the equation 2x – y = 6,we have
Substituting x = 2 and y = –2 in 2x – y, we get
is the solution of 2x – y = 6.
i v In the equation 2x – y = 6, we have
Substituting and y = 0 in 2x – y, we get
is not the solution of 2x – y = 6.
v In the equation 2x – y = 6, we have
( )
Substituting and y = –5 in 2x – y, we get
is the solution of 2x – y = 6.
Question:6
If x = -1, y = 2 is a solution of the equation 3x + 4y = k, find the value of k.
Solution:
We are given,
is the solution of equation .
Substituting and in ,we get
Question:7
Find the value of ?, if x = - ? and y =
5
2
is a solution of the equation x + 4y - 7 = 0.
Solution:
We are given,
is the solution of equation .
Substituting and in ,we get
Question:8
If x = 2 a + 1 and y = a - 1 is a solution of the equation 2x - 3y + 5 = 0, find the value of a .
Solution:
We are given,
is the solution of equation .
Substituting and in ,we get
Read More